Research on integrating language and content in diverse contexts - Christison, MaryAnn; Crandall, Jo Ann; Christian, Donna (New York, NY : Routledge : International Research Foundation for English Language Education (TIRF), 2022)
"Co-published with The International Research Foundation for English Language Education (TIRF), the ninth volume in the Global Research on Teaching and Learning English series presents research on the practice of integrating content and language in diverse contexts where English is used as a medium of instruction. With chapters written by TIRF Doctoral Dissertation Grant awardees and other scholars, the volume offers an overview of a wide range of methodological approaches to teaching content in English to English learners and examines factors that impede or contribute to effective instruction. The chapters include findings from original empirical research as well as overviews of existing research and model programs, providing valuable insights and taking into account a multitude of contextual features. Offering up-to-date research on integrating language and content at the primary, secondary, and post-secondary levels, this book familiarizes readers with the latest advances in theory and practice. It is a key text for teacher education courses for pre-service teachers, a resource for professional development programs for practicing teachers, and a useful reference for researchers"--
PART 1. Integrating Language and Content in Primary School Contexts. Working Towards a Multilingual Paradigm in Content Based English Language Teaching: Implications for Teacher Education -- The Bottom Group: How Teacher Expectations, Tracking, and Standards Contribute to EL Underrepresentation in STEM -- Are We Missing Part of the Picture? Assessing English Learners in Science From a Multimodal Perspective -- Digital Technologies and Storytelling for CLIL in a Primary School in Italy -- PART 2. Integrating Language and Content in Secondary School Contexts. Integrated Language and Content Instruction: Program Models in Secondary Schools -- Pooling Semiotic Resources Among Recently Arrived Immigrant Students in a High School Biology Class -- Teaching Language and Content in Chilean Vocational Education Training (VET) Schools: Exploring the Perspectives of Industry Professionals and EFL Teachers -- Information Classification: General 8 Preservice Science Teachers' Written Feedback Practices Following Preparation for "Sheltered" Instruction -- PART 3. Integrating Language and Content in Postsecondary Contexts. EMI Teacher Cognition: Exploring Lecturers' Experiences Across Europe -- Collaboration, Identity, and Internationalization: Professional Development for CLIL in Brazil -- An Investigation of Language Related Challenges in Full and Multilingual English Medium Instruction Models in Turkey -- Age of Onset, English Medium Instruction, and Gains in Second Language Grammar Knowledge -- Using a Design Thinking Approach for the Delivery of EMI Instruction for Preengineering Students in Palestine.
Keywords: Language transfer (Language learning); English language -- Study and teaching -- Foreign speakers; Interdisciplinary approach in education; FOREIGN LANGUAGE STUDY / General; EDUCATION / Language Experience Approach